Variant Trifurcation of the Ulnar Nerve in Guyon’s Canal of the Human Wrist: Case report - Fathi Ali, Tagreed; Musa Fadlelmula, Khalid (International Journal of Human Anatomy, 2021)
During routine dissection of the right hand of a 52-year-old Asian descent male cadaver in the Department of Anatomy at Jazan University-Faculty of Medicine, we observed an anatomical variation of the ulnar nerve (UN). There was a trifurcation of the nerve in the ulnar tunnel proximal to the pisiform bone. An awareness of such variation may be of great clinical importance despite the presence of trifurcation of the ulnar nerve, which does not usually cause symptoms but becomes important in the evaluation of entrapment neuropathy and during surgical and orthopedic interventions
Keywords: Ulnar nerve; Ulnar tunnel; Trifurcation; Pisiform bone.